If it's not what You are looking for type in the equation solver your own equation and let us solve it.
72+6x=x2
We move all terms to the left:
72+6x-(x2)=0
We add all the numbers together, and all the variables
-1x^2+6x+72=0
a = -1; b = 6; c = +72;
Δ = b2-4ac
Δ = 62-4·(-1)·72
Δ = 324
The delta value is higher than zero, so the equation has two solutions
We use following formulas to calculate our solutions:$x_{1}=\frac{-b-\sqrt{\Delta}}{2a}$$x_{2}=\frac{-b+\sqrt{\Delta}}{2a}$$\sqrt{\Delta}=\sqrt{324}=18$$x_{1}=\frac{-b-\sqrt{\Delta}}{2a}=\frac{-(6)-18}{2*-1}=\frac{-24}{-2} =+12 $$x_{2}=\frac{-b+\sqrt{\Delta}}{2a}=\frac{-(6)+18}{2*-1}=\frac{12}{-2} =-6 $
| 4x-40=7(-2x+20) | | 9x^2+31=-50 | | p-3=7-3-p-5p | | 5x+7+20=4 | | y=11^2-6 | | 2r+3(3r-4)=-45 | | 42=6x-25 | | 33+15w=3w−w+4ww= | | C=0.09x+12.50 | | -12s-12=-19s+2 | | 0.05x+19.95=23.74 | | x4=2 | | -12+4x=-7 | | -5y-3=-2(y+7) | | y=-11^2-6 | | r+2=-15+4-6r-6r | | 1/3(x-7)=2 | | 2x=−1 | | 0=12x-1 | | -8-2(-x-2)=10 | | 4+3(x-12)=88 | | 4-6(3h+2)=1-(5-7h) | | -11=1-6w | | -7(6x-2)=-42x-14 | | 2x+3+x=5x-2-2x | | Y=2y+2y+88 | | x-33=x+44 | | 250+50x=400+40x | | 14j+8=-16j | | 4x-17=6x-92 | | k/11=-5 | | 11-12z-5=-10z-16 |